1999
DOI: 10.1007/bf03012545
|View full text |Cite
|
Sign up to set email alerts
|

The anesthetic record: accuracy and completeness

Abstract: RRTPurpose: To evaluate if anesthesia training and experience influenced chart completion and accuracy. Methods: One hundred and twenty-four subjects, including medical students, anesthesia residents and community and university based clinical anesthesiologists, were given a standardized patient in a simulator environment and asked to conduct induction and maintenance of anaesthesia. Three critical events were introduced resulting in changes in BP, HR, PETCO~ and SpOt. Subjects were instructed to manage the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 12 publications
(3 reference statements)
3
32
2
1
Order By: Relevance
“…However, while deficiencies in certain aspects of the record have been noted 3 and the incidence of properly complete anaesthetic records has been reported as being <35%, 4 none of them has reported such a high incidence of total absence of any form of anaesthetic record as found in this survey. One study, which reported an overall acceptable level of anaesthetic recordkeeping of 72% with only 1% of the records being illegible, commented that standards of anaesthetic record-keeping needed to be improved, particularly for the preoperative period.…”
Section: Discussioncontrasting
confidence: 48%
“…However, while deficiencies in certain aspects of the record have been noted 3 and the incidence of properly complete anaesthetic records has been reported as being <35%, 4 none of them has reported such a high incidence of total absence of any form of anaesthetic record as found in this survey. One study, which reported an overall acceptable level of anaesthetic recordkeeping of 72% with only 1% of the records being illegible, commented that standards of anaesthetic record-keeping needed to be improved, particularly for the preoperative period.…”
Section: Discussioncontrasting
confidence: 48%
“…Even today, many centers still utilize hand-written records with data recorded every 10 and 15 minutes. These data records are currently considered to be an accurate representation of the bypass period; however, upon investigation, they appear to represent a blending of data points towards accepted norms and a minimization of outlier data points (54,55). Once these patient specific and frequent data points are available, they can to be used in conjunction with other clinical databases such as the Society of Thoracic Surgeons Congenital Heart Surgery (STS) (56), Pediatric Cardiac Critical Care Consortium (PC4) (57,58), and Pediatric Acute Care Cardiology Collaborative (PAC3) (59-61), and Extracorporeal Life Support Organization Registry (ELSO) (62,63) to examine the relationships between patient parameters and practices utilized during CPB with short and long term patient outcomes (64).…”
Section: Physical Parameter Measurements and Data Capturementioning
confidence: 99%
“…38 Common problems of poor recordkeeping included the omission of abnormal values, the smoothing or rounding of abnormal values to within the expected upper or lower limits, and the averaging of measurements around an abnormal value, thereby reducing the precision of a single abnormal value.…”
Section: Anesthesia Information Management Systems (Aims)mentioning
confidence: 99%